Dental Students’ Awareness and Attitudes Towards Patients’ Safety Culture in Tertiary Care Dental Hospitals - Memoona Amin, Aiman Zahid, Muhammad Imtiaz, Salima Naveed Manji, Hafiz Fawaz Nadeem, Waleed Khalid, (Pakistan Journal of Medical & Health Sciences, 2023)
Objective: Patient safety culture is a mature concept but is new to dentistry and an important component to enhance the quality of life. This study aims to evaluate dental students' awareness and attitudes toward the patient safety culture in the FMH College of Dentistry, Lahore Pakistan. Methods: This cross-sectional study was conducted on 396 participants from different public (40)% and private (60)% institutes of Pakistan from January 2022 to December 2022 using the safety attitude questionnaire (SAQ) having six domains: teamwork climate, job satisfaction, perception of management, stress recognition, safety climate, and working conditions. Results: This study included 60.2% of BDS 3rd year and 39.8% of BDS 4th year students of different public and private tertiary care dental hospitals. Results showed the highest mean (3.7015) in the stress level among students and job satisfaction as participants were satisfied with their jobs, showing a mean value of 3.65. Comparison between the public and private sectors showed that teamwork climate (P value 0.400) and job satisfaction (P value 0.445) have no difference and the remaining domains were better in the private sector. Conclusion: The study showed a positive response to patient safety. Participants were satisfied with their job but their stress level was also high. In the private sector, work conditions were much better than in the public sector. But my stress level was also high. Safety culture and perception of management were slightly higher in the private sector. Keywords: Patient safety, dental students, dental education, dental public health, dental errors, dentistry, patient safety culture, educational methods, health services research